KRITIK HOLISTIK PADA LUKISAN VITALITAS KARYA BAGAS RACHELMA TAHUN 2024 - putri, nabila ans winda (Ars: Jurnal Seni Rupa dan Desain, 2025)
A work of art undoubtedly has a background of its creation and the values it contains. The effort to discover the background of its creation and the values within the artwork is conducted through art criticism activities. The research titled "Holistic Critique of the Painting 'Vitalitas' by Bagas Rachelma 2024" employs a holistic critique approach to uncover Bagas's background in creating the painting 'Vitalitas' and to identify the values it contains. The method used in this study is descriptive qualitative with a holistic critique approach. The data sources for this research include the artist who created the artwork and several supporting documents. The findings of this study indicate that Bagas Rachelma created this painting to convey the artist's emotional message and to progress in their artistic journey. The values contained in this work include personal expression, emotional value, the artist's character, and the medium of freedom of expression.